Lamina cribrosa surface position in idiopathic intracranial hypertension with swept-source optical coherence tomography - Pasaoglu, Isil (Indian J Ophthalmol, 2019)
PURPOSE: The purpose of this study is to compare the thickness and depth measurements of the lamina cribrosa (LC) obtained using a swept-source optical coherence tomography (SS-OCT) device in idiopathic intracranial hypertension (IIH) patients and healthy subjects. METHODS: This retrospective, cross-sectional observational study included 16 eyes with IIH and 20 control eyes. The LC measurements with serial horizontal B scans of the optic nerve head were obtained using SS-OCT (Topcon 3D DRI OCT Triton). The anterior lamina surface (ALS) depth, posterior lamina surface (PLS) depth, and LC thickness measurements were evaluated. RESULTS: In patients with IIH, the mean ALS depth was 225.00 ± 58.57 μm and the mean PLS depth was 449.75 ± 63.50 μm. In the IIH control group, the corresponding values were 359.40 ± 105.38 and 570.10 ± 99.41 μm (P < 0.05). The difference in LC thickness between the IIH and control subjects was not statistically significant. CONCLUSION: LC can be evaluated using an SS-OCT device. LC was displaced anteriorly in patients with IIH compared with normal controls. The assessment of LC level with SS-OCT in IIH cases is a valuable and reproducible adjunctive imaging method in terms of diagnosis and follow-up.